FAKTOR-FAKTOR YANG MEMPENGARUHI DAYA TAHAN MAHASISWA TEKNIK SIPIL UIB DALAM MEMPERTAHANKAN STUDINYA - HUDORI, MAHFUZ (E-Jurnal Matematika; Vol 10 No 1 (2021)DO - 10.24843/MTK.2021.v10.i01.p312, 2021)
Linear regression model cannot be used to analyze the relationship between survival time and independent variables, it is because the linear regression model is not able to handle censored data. Regression can be used to analyze survival data is cox proportional hazard regression. This research studies factors that influence study time drop out of Civil Engineering students at Universitas International Batam using the cox proportional hazard regression model approach. The independent variable that influenced study time drop out of Civil Engineering students at Universitas International Batam was the Cumulative Achievement Index and Work Status.